Improving lithium polysulfides redox with spinel oxides for lithium-sulfur batteries - Shen, Chen (Nanyang Technological University, 2020)
Lithium-sulfur (Li-S) batteries have been recognized as potential candidates for next-generation rechargeable cells because of their high energy density. However, polysulfides’ ‘shuttle effect’ and sluggish redox kinetics at cathode induced low sulfur utilization, severe capacity decay and short cycling life. In order to suppress shuttle effect, spinel oxides (AB_2 O_4) were incorporated into sulfur cathodes. Spinel oxides were proved to increase lithium polysulfides (LiPSs) adsorption and facilitate polysulfides redox reaction. Those spinel oxides include MgCo_2 O_4, FeCo_2 O_4, ZnCo_2 O_4 and Co_3 O_4. MgCo_2 O_4 exhibited strong adsorption of LiPS in static adsorption of polysulfides. The basicity of MgCo_2 O_4 enabled its superior affinity with polar polysulfides. In nucleation of Li_2 S_8, more Li_2 S_8 was adsorbed onto the cathodes with spinel oxides and converted in the redox reactions. The effect of basicity of spinel oxides on LiPS adsorption was further validated. High polysulfide reactivity of spinel oxides contributed to effective polarization mitigation in cyclic voltammograms for spinel oxide symmetrical cells. Excellent cycling performance of cell with spinel oxides confirmed spinel oxides’ LiPS adsorption ability and catalytic activity in Li-S redox reactions. This report wished to provide new insights into polysulfide adsorption and polysulfide reactivity in cathodic redox reactions.